2021
DOI: 10.3233/sji-210841
|View full text |Cite
|
Sign up to set email alerts
|

Data science training for official statistics: A new scientific paradigm of information and knowledge development in national statistical systems

Abstract: The ability to incorporate new and Big Data sources and to benefit from emerging technologies such as Web Technologies, Remote Data Collection methods, User Experience Platforms, and Trusted Smart Statistics will become increasingly important in producing and disseminating official statistics. The skills and competencies required to automate, analyse, and optimize such complex systems are often not part of the traditional skill set of most National Statistical Offices. The adoption of these technologies requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Now, the correlation coefficient increased dramatically to 94% ( -value 0.000), which can be attributed to the higher quality of the official statistics in these countries. Ashofteh and Bravo (2020) have shown there to be significant variation in the quality of the COVID-19 datasets reported worldwide, albeit a recent study suggests that data science and new technologies can be expected to play a significant role in improving data quality from national statistical offices in the future [52] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, the correlation coefficient increased dramatically to 94% ( -value 0.000), which can be attributed to the higher quality of the official statistics in these countries. Ashofteh and Bravo (2020) have shown there to be significant variation in the quality of the COVID-19 datasets reported worldwide, albeit a recent study suggests that data science and new technologies can be expected to play a significant role in improving data quality from national statistical offices in the future [52] .…”
Section: Resultsmentioning
confidence: 99%
“…Ashofteh and Bravo (2020) showed that there is significant variation in the quality of COVID-19 datasets reported worldwide. A recent study suggests that data science and new technologies are expected to play a significant role in improving data quality at National Statistical Offices in the future [53].…”
Section: Row Countrymentioning
confidence: 99%
“…With the development of information technology, big data has become an indispensable tool for processing and analyzing large amounts of data [8][9]. It becomes particularly important to find patterns or screen out valuable information in redundant and mixed massive information [10][11].…”
Section: Big Datamentioning
confidence: 99%
“…Today, National Statistical Institutes (NSIs) face challenges and changes in the way they produce official statistics (Radermacher 2020). On the one hand, technological developments create the opportunity for paradigm shifts in methodology (Ashofteh and Bravo 2021). On the other hand, modern societal changes and challenges create new user demands for high-quality data and statistics (Cai and Zhu 2015).…”
Section: Introductionmentioning
confidence: 99%